A Scoping Review of Health Outcomes Examined in Randomized Controlled Trials Using Guided Imagery. Issue 7 (December 2017) - Giacobbi, Peter R.; Stewart, Jonathan; Chaffee, Keeley; Jaeschke, Anna-Marie; Stabler, Meagan; Kelley, George A.
Abstract : Introduction: Guided imagery involves the controlled visualization of detailed mental images. This integrative health technique is used for healing, health maintenance, or the treatment of specific conditions. Guided imagery is an integral part of mindfulness meditation, hypnosis, and various relaxation exercises. However, evidence to support the widespread use and dissemination of guided imagery interventions has been lacking. The purposes of this scoping review were to document the scope of health outcomes and disease processes examined by guided imagery researchers and the journal outlets where this work has been published. Secondary purposes were to review the efficacy of guided imagery, risk of bias from studies published in selected integrative health journals, and gain feedback from clinicians in a practiced-based research network about potential barriers for use in clinical settings. Methods: Ten bibliographic databases were searched for randomized controlled trials (RCTs) published between 1960 and 2013 that included adult participants. Descriptive and analytic methods were employed to document the journal outlets, diseases, and health outcomes investigated. Results: Three hundred twenty RCTs that included more than 17, 979 adult participants were reviewed. The published studies appeared in 216 peer-reviewed journals from diverse disciplines largely representing psychology, the sport sciences, rehabilitation, nursing, and medicine. Major outcomes observed were coping with pain, stroke recovery, anxiety, coping with stress, and sport skills. Practitioner feedback from the practiced-based research network revealed some interest but skepticism and time constraints were discussed as barriers. Conclusions: Ongoing research and creative dissemination techniques are warranted. Abstract : Supplemental Digital Content is available in the text.